POWERFUL EFFORT OF THE COAST COMMUNITY THROUGH GENDER APPROACH - Maria E. Pandu (SOCIUS : Jurnal Sosiologi, 2013)
The fishermen families are a part of society. Unfortunately, they live in a minimum income. Therefore, sometimes some of them do subsidiary work to fulfill their needs. This study done at Dusun Kampala Desa Bonto Mate’ne as a part of coastal community where the fishermen family are working. The method used is the mixed; the quantitative and qualitative approach. This study aims to know more about social economy of Dusun Kampala's people as a coast village, to know more about the relationship and role of household members base on the gender perspective domestic or public and to know more about the function of local institutions, informal and formal in Dusun Kampala's social activities. The research determine that base on its natural resources condition, then the main livelihood of Dusun Kampala's people is fishery which are consist of 4 kinds of work grouping: as ponggawa, sawi, padallekang, and fishponder, the level of knowledge and low technology application and also of natural factors likeflood in every rainy season affect to the live of fishermen, and the women usually have expanded skill, but less opportunity to actualize themselves and need consultation, training and enlightening.Key word : social welfare, house hold, fishermen, local institution, social net, gender relation, local value